Translational Potential of Epigenetic-Based Markers on Fine-Needle Aspiration Thyroid Specimens - Canberk, Sule; Lima, Ana Rita; Pinto, Mafalda; Máximo, Valdemar (Frontiers in Medicine, 2021)
The awareness of epigenetic alterations leading to neoplasia attracted the attention of researchers towards its potential use in the management of cancer, from diagnosis to prognosis and prediction of response to therapies. Our group has focused its attention into the epigenomics of thyroid neoplasms. Although most of the epigenetic studies have been applied on histological samples, the fact is that cytology, through fine needle aspiration (FNA), is a primary diagnostic method for many pathologies, of which thyroid nodules is one of the most paradigmatic examples. This has led to an increasingly report, in the literature, of epigenetic studies using these biological samples over the past decade. In this review, our group aimed to document recent research of epigenetic alterations and its associated assessment techniques, based on cytology material. Our review covers the main epigenetic categories - DNA methylation, histone modification and RNA-silencing -, whose evidence in thyroid cytology samples may represent solid soil for future prospectively designed studies aiming at validating patterns of epigenetic alterations and its potential use in the clinical management of thyroid neoplasms.